Stunting, wasting and associated factors among children aged 6-24 months in Dabat health and demographic surveillance system site: A community based cross-sectional study in Ethiopia - Terefe Derso; Amare Tariku; Gashaw Andargie Biks; Molla Mesele Wassie (BMC, 2017)
Abstract Background Though there is a marked decline in burden of undernutrition, about 44 and 10% of children under five are stunted and wasted, respectively in Ethiopia. The highest prevalence of wasting occurs in young children (6-23 months), however literature are limited in these population groups. Therefore, this study aimed to assess stunting, wasting and associated factors among children aged 6-24 months in Dabat Health and Demographic Surveillance System (HDSS) site, northwest Ethiopia. Methods A community based cross-sectional study was conducted in Dabat HDSS site from May 01 to June 29, 2015. A total of 587 mother-child pairs were included in the study. A multivariate logistic regression analysis was carried out to identify factors associated with stunting and wasting, separately. Results The prevalence of stunting and wasting among children aged 6-24 months were 58.1 and 17.0%, respectively. Poor wealth status [Adjusted Odds Ratio (AOR) = 2.20; 95% Confidence Interval (CI): 1.42, 3.40], unavailability of latrine [AOR = 1.76; 95% CI: 1.17, 2.66], child age: 12-24 months [AOR = 3.24; 95% CI: 2.24, 4.69], not receiving maternal postnatal vitamin-A supplementation [AOR = 1.54; 95%: 1.02, 2.33] and source of family food: own food production [AOR = 1.71; 95% CI: 1.14, 2.57] were significantly associated with higher odds of stunting. However, only history of diarrheal morbidity was significantly associated with wasting [AOR = 2.06; 95% CI: 1.29, 3.30]. Conclusions In this community, the magnitude of stunting and wasting exists as a severe public health concern. Therefore, improving socio-economic status, latrine and maternal postnatal vitamin-supplementation coverage are essential to mitigate the high burden of stunting. Besides, reducing the childhood diarrheal morbidity as well as strengthening early diagnosis and management of the problem are crucial to curve the high prevalence of wasting.